2022
DOI: 10.3389/fphar.2021.832673
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Cardio-Cerebrovascular Diseases of Ligusticum chuanxiong Hort.

Abstract: Cardio-cerebrovascular diseases (CVDs) are a serious threat to human health and account for 31% of global mortality. Ligusticum chuanxiong Hort. (CX) is derived from umbellifer plants. Its rhizome, leaves, and fibrous roots are similar in composition but have different contents. It has been used in Japanese, Korean, and other traditional medicine for over 2000 years. Currently, it is mostly cultivated and has high safety and low side effects. Due to the lack of a systematic summary of the efficacy of CX in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 213 publications
0
21
0
Order By: Relevance
“…As shown in Figure 1 A and 1 B , 12 compounds were characterized by LC/MS, including 1 Ligustrazine (m/z = 136.19; rt = 0.88 min), 2 D-Arabitol (m/z = 152.15; rt = 0.926 min), 3 Isoleucine (m/z = 13.17; rt = 2.11 min), 4 Folic acid (m/z = 441.4; rt = 5.117 min), 5 Caffeic acid (m/z = 180.16; rt = 5.801 min), 6 Sodium ferulate (m/z = 216.17; rt = 6.81 min), 7 Ferulic acid (m/z=194.19; rt = 6.881 min), 8 Isochlorogenic acid A (m/z = 516.45;rt = 6.912 min), 9 Isovanillin (m/z = 152.15; rt = 7.676 min), 10 Senkyunolide A (m/z = 192.25; rt = 10.97 min), 11 Ligustilide (m/z = 190.23; rt = 11.86 min), 12 Levistilide A (m/z = 380.48; rt = 13.75 min). The CX extract indicated that the sample used in this experiment contained the active ingredients described in previous research ( Li et al, 2021 ).
Figure 1 Compounds characterization of CX extract and dose-dependent effects of CX extract on angiogenesis of preovulatory follicles.
…”
Section: Resultsmentioning
confidence: 72%
“…As shown in Figure 1 A and 1 B , 12 compounds were characterized by LC/MS, including 1 Ligustrazine (m/z = 136.19; rt = 0.88 min), 2 D-Arabitol (m/z = 152.15; rt = 0.926 min), 3 Isoleucine (m/z = 13.17; rt = 2.11 min), 4 Folic acid (m/z = 441.4; rt = 5.117 min), 5 Caffeic acid (m/z = 180.16; rt = 5.801 min), 6 Sodium ferulate (m/z = 216.17; rt = 6.81 min), 7 Ferulic acid (m/z=194.19; rt = 6.881 min), 8 Isochlorogenic acid A (m/z = 516.45;rt = 6.912 min), 9 Isovanillin (m/z = 152.15; rt = 7.676 min), 10 Senkyunolide A (m/z = 192.25; rt = 10.97 min), 11 Ligustilide (m/z = 190.23; rt = 11.86 min), 12 Levistilide A (m/z = 380.48; rt = 13.75 min). The CX extract indicated that the sample used in this experiment contained the active ingredients described in previous research ( Li et al, 2021 ).
Figure 1 Compounds characterization of CX extract and dose-dependent effects of CX extract on angiogenesis of preovulatory follicles.
…”
Section: Resultsmentioning
confidence: 72%
“…The rhizome, leaves, and fibrous roots of L. chuanxiong Hort. are similar in composition but have different contents [ 30 ].…”
Section: Chemical Componentsmentioning
confidence: 99%
“…A range of concentrations between 250 and 1000 g/mL of leaves and rhizome of CX were found to be safe for C. elegans . These concentrations did not affect worm viability after 24 h when compared with the control group; the leaf and root of CX are safe as medicinal and edible plant foods [ 30 , 80 , 81 ]. Moreover, it has been used in Japanese, Korean, and other traditional medicine for over 2000 years.…”
Section: Food Safety Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of the severe personal and social burden caused by neurological and psychiatric disorders, efforts should be made to provide solutions to benefit patients. In order to fulfill the demand for disease-oriented therapies, mechanism-oriented therapies must be implemented on the supply side ( 4 ). Mechanism-oriented therapy is the basis and the means, while disease-oriented therapy is the end and the way out, and they are not contradictory.…”
Section: Introductionmentioning
confidence: 99%